The critical role of Rap1-GAPs Rasa3 and Sipa1 in T cells for pulmonary transit and egress from the lymph nodes - Horitani, Shunsuke; Ueda, Yoshihiro; Kamioka, Yuji; Kondo, Naoyuki; Ikeda, Yoshiki; Naganuma, Makoto; Kinashi, Tatsuo (Frontiers in Immunology, 2023)
Rap1-GTPase activates integrins and plays an indispensable role in lymphocyte trafficking, but the importance of Rap1 inactivation in this process remains unknown.Here we identified the Rap1-inactivating proteins Rasa3 and Sipa1 as critical regulators of lymphocyte trafficking. The loss of Rasa3 and Sipa1 in T cells induced spontaneous Rap1 activation and adhesion. As a consequence, T cells deficient in Rasa3 and Sipa1 were trapped in the lung due to firm attachment to capillary beds, while administration of LFA1 antibodies or loss of talin1 or Rap1 rescued lung sequestration. Unexpectedly, mutant T cells exhibited normal extravasation into lymph nodes, fast interstitial migration, even greater chemotactic responses to chemokines and sphingosine-1-phosphate, and entrance into lymphatic sinuses but severely delayed exit: mutant T cells retained high motility in lymphatic sinuses and frequently returned to the lymph node parenchyma, resulting in defective egress. These results reveal the critical trafficking processes that require Rap1 inactivation.